2 Assessing the Politics of Neo‐Assyrian Agriculture. Issue 1 (2nd July 2018) - Rosenzweig, Melissa S.
ABSTRACT: In this paper, political ecology informs a study of agriculture under the Neo‐Assyrian empire. Rather than examining cultivation solely as an economy of subsistence practices, this work considers agrarian laborers, activities, and resources as participants in wider political processes of empire‐building. Both material and discursive manipulations of agriculture are discussed in order to demonstrate the ways in which rulers of Neo‐Assyria instituted agricultural colonization in Upper Mesopotamia for political gain. An archaeobotanical case study from the provincial capital of Tušhan is then presented to provide a closer look at the impact of these agro‐politics on the people and lands in the provinces of the empire. Plant use studies from Tušhan capture the flow of power through agricultural practice, emphasize the Neo‐Assyrian monarchy's rhetorical use of agriculture in strategies of imperialism, and, significantly, reveal the shortcomings of the empire's agrarian program.